PENGARUH KUALITAS PRODUK, IKLAN, DAN SOCIAL INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE VIVO PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH BENGKULU - Ajis, Tika Melany; Ekowati, Sri (Yayasan Insani Mandiri Santani, 2020)
This study aims to determine the effect of product quality, advertisements, and social influencers on purchasing decisions for Vivo smartphones for students at Muhammadiyah Bengkulu University. The sample in this study were 200 students of Muhammadiyah Bengkulu University who used Vivo smartphones. Sampling using a questionnaire. The analysis technique used is multiple linear regression, coefficient of determination and hypothesis testing. The results showed that from the calculation of the multiple linear regression equation, it can be seen that the direction of the regression has a positive value with the equation Y = 3,968 + 0.495 (X_1) + 0.135 (X2) + 0.172 (X3). The coefficient of determination R Square (R ^ 2) obtained a value of 0.643 which means that the Product Quality (X_1), Advertising (X2) and Social influencer (X3) variables to the Purchase Decision variable contributed 0.643 or 64.3% to the Purchasing Decision. while the remaining 35.7% is influenced by other variables not included in this research model. Product quality has a positive effect on purchasing decisions for Vivo smartphones for students at the Muhammadiyah University of Bengkulu. Advertising has a positive effect on purchasing decisions for Vivo smartphones for students at the Muhammadiyah University of Bengkulu. Social influencers have a positive effect on purchasing decisions for Vivo smartphones for students at the Muhammadiyah University of Bengkulu. Product quality (X_1), advertisements (X2), and social influencers (X3) together have a positive effect on Purchasing Decision (Y) for Vivo smartphones for students at Muhammadiyah Bengkulu University because the significant value is smaller than 0.05.Â Keywords: Product Quality, Advertising, Social Influencer, Purchase Decision